Assessing the Impact of Environmental Waste Policies on Manufacturing Industry Practices - A. Nur As Adi; Anis Mutia; Rahmawati Rahmawati; Ilham Abu (CV. Sakura Digital Nusantara, 2024)
This study aims to evaluate the effect of waste management policies on manufacturing industry practices in Makassar City. This policy was implemented to regulate the disposal, treatment and recycling of industrial waste to reduce negative impacts on the environment and public health. Although this policy has been implemented, there are challenges in its implementation, such as technological limitations, high implementation costs, and lack of coordination between government agencies and industries. Qualitative methods were used in this study, with in-depth interviews with government representatives, industry managers, and affected communities. The results show that this policy has encouraged some industries to adopt environmentally friendly technologies, but there are still significant barriers that hinder the full effectiveness of this policy. To improve the effectiveness of the policy, recommendations include improved access to technology, more consistent enforcement of regulations, public education, and financial and infrastructure support. This research provides valuable insights for policy makers and industry practitioners in developing more effective and sustainable waste management strategies.